E-directory display (E-DD) - Rosman, Maisarah Farihin; Azman, Nur Adriana Athirah; Shari, Sharunizam (Universiti Teknologi MARA, Kedah, 2017)
An e-directory display (E-DD) is an electronic device that can be used in all libraries. It usually placed in shopping malls, but in this situation, we would like to use the directory in the library to help the users or students to search for items, know about the latest materials that has been used and help them to renew or borrow the books that they want. Because of nowadays electronic devices and gadgets are so popular, it can attract more users to use the devices. Touch screen devices and it can turn off and on by itself when the library are closed/open.